Roma populations and health inequalities: a new perspective. Issue 5 (28th November 2019) - Orton, Lois; Anderson de Cuevas, Rachel; Stojanovski, Kristefer; Gamella, Juan F.; Greenfields, Margaret; La Parra, Daniel; Marcu, Oana; Matras, Yaron; Donert, Celia; Frost, Diane; Robinson, Jude; Rosenhaft, Eve; et al.
Abstract : Purpose: The purpose of this paper is to explore the emergence of "Roma health and wellbeing" as a focus of attention in European research and in policy and the possible detrimental consequences of action founded on a generic representation of "Roma health." Design/methodology/approach: Based on discussions with and research conducted by scholars who work directly with Roma communities across European regions from a wide range of academic disciplines it suggests how future research might inform: a more nuanced understanding of the causes of poor health and wellbeing among diverse Roma populations and; actions that may have greater potential to improve the health and wellbeing among these populations. Findings: In summary, the authors promote three types of research: first critical analyses that unpick the implications of current and past representations of "Roma" and "Roma health." Second, applied participatory research that meaningfully involves people from specific self-defined Roma populations to identify important issues for their health and wellbeing. Third, learning about processes that might impact on the health and wellbeing of Roma populations from research with other populations in similarly excluded situations. Originality/value: The authors provide a multidisciplinary perspective to inform research that does not perpetuate further alienation and prejudice, but promotes urgent action to redress the social and health injustices experienced by diverse Roma populations across Europe.